2020
DOI: 10.1002/smll.201906206
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizic‐Acid‐Based Carbon Dots with High Antiviral Activity by Multisite Inhibition Mechanisms

Abstract: With the gradual usage of carbon dots (CDs) in the area of antiviral research, attempts have been stepped up to develop new antiviral CDs with high biocompatibility and antiviral effects. In this study, a kind of highly biocompatible CDs (Gly‐CDs) is synthesized from active ingredient (glycyrrhizic acid) of Chinese herbal medicine by a hydrothermal method. Using the porcine reproductive and respiratory syndrome virus (PRRSV) as a model, it is found that the Gly‐CDs inhibit PRRSV proliferation by up to 5 orders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
176
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(179 citation statements)
references
References 86 publications
(107 reference statements)
3
176
0
Order By: Relevance
“…As shown in the results, one-step heating of curcumin at 180°C preserves many of the moieties of polymeric curcumin on the surfaces of the as-synthesized Cur-CQDs, resulting in superior antiviral characteristics. Later, our group has developed a new type of highly biocompatible carbon quantum dots (Gly-CDs) with glycyrrhizic acid (an active ingredient of Chinese herbal medicine) using a hydrothermal method, and the as-prepared Gly-CDs were shown to inhibit the proliferation of PRRSV by up to 5 orders of viral titers [52]. Further investigations reveal that Gly-CDs can inhibit PRRSV invasion and replication, stimulate antiviral innate immune responses, and suppress the accumulation of intracellular reactive oxygen species (ROS) caused by PRRSV infection.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…As shown in the results, one-step heating of curcumin at 180°C preserves many of the moieties of polymeric curcumin on the surfaces of the as-synthesized Cur-CQDs, resulting in superior antiviral characteristics. Later, our group has developed a new type of highly biocompatible carbon quantum dots (Gly-CDs) with glycyrrhizic acid (an active ingredient of Chinese herbal medicine) using a hydrothermal method, and the as-prepared Gly-CDs were shown to inhibit the proliferation of PRRSV by up to 5 orders of viral titers [52]. Further investigations reveal that Gly-CDs can inhibit PRRSV invasion and replication, stimulate antiviral innate immune responses, and suppress the accumulation of intracellular reactive oxygen species (ROS) caused by PRRSV infection.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…[29] Similarly, the Gly-CDs derived from glycyrrhizic acid exerted excellent antiviral properties by suppressing the propagation of porcine reproductive and respiratory syndrome virus. [30] In addition, the use of conventional biocompounds (e.g. curcumin) in the synthesis of QDs can offer a suitable choice of antiviral agents.…”
Section: Mode Of Actions Of Qdsmentioning
confidence: 99%
“…Functional carbon dots as antiviral agents: Several antiviral therapeutics are recently being developed around the World, based on carbon dots or carbon quantum dots, initially discovered for its colorful and bright fluorescence resembling the conventional semiconductor quantum dots [49] , [53] , [54] , [55] .…”
Section: Nanomaterials As Viral Entry Inhibitorsmentioning
confidence: 99%
“…In a more recent study, Tong et al. investigated the effect of Glycyrrhizic acid-based carbon dots(Gly-CDs) upon the invasion potential of PSRRV(Porcine reproductive and respiratory syndrome virus) using African green monkey kidney(Vero) and Porcine Kidney(PK-15) cells [55] . Through TEM, they concluded that Gly-CDs could directly interact with the PSRRVs, adding to the virus’s reduced infectivity due to Gly-CD treatment.…”
Section: Nanomaterials As Viral Entry Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation